Trajetória de consolidação na produção científica do Pesquisador sênior - COSTA, Renato Pinheiro da (Universidade Federal do Pará, 2017)
This study aimed to understand the consolidation trajectories of the careers of senior researchers from the National Scientific and Technological Development Council - CNPq linked to the education sector as well as the interests that mobilize in scientific production. The specific objectives were: To analyze under what circumstances occur the production of researchers in the scientific context; identify the bonds of institutional guidelines CNPQ incentive policy and fostering research in the country; understand how scientific knowledge has been produced together with the development of the interests of researchers in the field of education and policies of development institutions; reflect on the career and productivity of senior category researchers Education Area. The study is based on documentary and bibliographical research, with the theoretical framework Jürgen Habermas and his discussion on the theory of knowledge and interest; still scrutinizes historical sources of theses, dissertations, books, scientific articles published in journals, proceedings and events and Lattes of researchers senior presenting the operational structure of the agencies for research. As is historically built the career of the researcher especially the education area linked to CNPq? What are the interests involved in the constitution of the senior research career? What are the prevailing epistemological basis in scientific production of the education sector researchers with this profile? The senior is the reference in the development of research and scientific productivity according to the Normative Resolutions of the CNPq? How delineation of a historical time research is developed in the period between the years 2006 to 2016. It is presented as a thesis the argument that the scientific productions of senior researchers are forged through appropriations epistemological, ideological and political order, developed in context of modernity which introduces the formation of the subject from relationships with society and its institutions, leaving telltale traces of their profiles related to the training course, the fluctuation in the linearity of the literature they produce, the choice of the type of publication of the result of his research, which shows that the knowledge they produce is only developed by interests. It was concluded that the research career has been built historicallybetween the introduction of political projects of the State through the funding agencies and related institutions that structure, to promote science and technology and the establishment and organization of a community around the development of the scientific field, making institutional structures as researchers classification were created in order to promote the recognition of the intensive work of those engaged in the promotion of scientific knowledge, as in the case of researchers from senior mode.